Penguatan Literasi Digital Siswa melalui Pendekatan Participatory Action Research di MA Laboratorium Kota Jambi - Fibrika Rahmat Basuki; Zainal Hartoyo; Abd Rahim; Salman Al Farisi (Jurnal Surya Masyarakat, 2026)
The rapid development of digital technology has had a significant impact on students’ lives, both in learning processes and social interactions. However, various studies indicate that students' digital literacy in Indonesia remains relatively low, particularly in technical skills, media ethics, and cybersecurity awareness. This condition increases students’ vulnerability to misinformation (hoaxes), misuse of social media, and underutilization of technology for productive learning. This Community Service Program (Pengabdian kepada Masyarakat/PkM) aims to strengthen students' digital literacy at MA Laboratorium Kota Jambi. The program employs a Participatory Action Research (PAR) approach, which emphasizes the active involvement of participants at all stages, including needs identification, planning, implementation, and evaluation. The PKM activities include training in digital ethics and cybersecurity, using Microsoft Office, the internet, and artificial intelligence (AI), graphic design with Canva, and basic videography skills. All activities were conducted interactively through hands-on practice, discussions, and small-group mentoring. The evaluation results, based on questionnaire data, indicate a significant improvement across all aspects of digital literacy, including technical skills, digital security awareness, media ethics, information verification, and creative abilities in producing digital content. Participants also demonstrated increased motivation to utilize technology to support learning activities and student organizations. Overall, this PKM successfully strengthened students’ digital competencies and laid a foundation for sustainable digital literacy programs at the madrasah level.